Removal of Reprogramming Transgenes Improves the Tissue Reconstitution Potential of Keratinocytes Generated From Human Induced Pluripotent Stem Cells. (14th July 2014) - Igawa, Ken; Kokubu, Chikara; Yusa, Kosuke; Horie, Kyoji; Yoshimura, Yasuhide; Yamauchi, Kaori; Suemori, Hirofumi; Yokozeki, Hiroo; Toyoda, Masashi; Kiyokawa, Nobutaka; Okita, Hajime; Miyagawa, Yoshitaka; et al.
Abstract : Morphological, functional, and molecular analyses including single-cell gene expression profiling revealed that keratinocytes from transgene-free human induced pluripotent stem cell (hiPSC) lines were more similar to normal human keratinocytes than those from transgene-residual hiPSC lines, which may be partly explained by reactivation of residual transgenes upon induction of keratinocyte differentiation. These results suggest that transgene-free hiPSC lines should be chosen for therapeutic purposes. Abstract: : Human induced pluripotent stem cell (hiPSC) lines have a great potential for therapeutics because customized cells and organs can be induced from such cells. Assessment of the residual reprogramming factors after the generation of hiPSC lines is required, but an ideal system has been lacking. Here, we generated hiPSC lines from normal human dermal fibroblasts with piggyBac transposon bearing reprogramming transgenes followed by removal of the transposon by the transposase. Under this condition, we compared the phenotypes of transgene-residual and -free hiPSCs of the same genetic background. The transgene-residual hiPSCs, in which the transcription levels of the reprogramming transgenes were eventually suppressed, were quite similar to the transgene-free hiPSCs in a pluripotent state. However, after differentiation into keratinocytes, clear differences were observed. Morphological, functional, and molecular analyses including single-cell gene expression profiling revealed that keratinocytes from transgene-free hiPSC lines were more similar to normal human keratinocytes than those from transgene-residual hiPSC lines, which may be partly explained by reactivation of residual transgenes upon induction of keratinocyte differentiation. These results suggest that transgene-free hiPSC lines should be chosen for therapeutic purposes.